Design of an Artificial Peptide Inspired by Transmembrane Mitochondrial Protein for Escorting Exogenous DNA into the Mitochondria to Restore their Functions by Simultaneous Multiple Gene Expression - Yoshinaga, Naoto; Miyamoto, Takaaki; Odahara, Masaki; Takeda‐Kamiya, Noriko; Toyooka, Kiminori; Nara, Seia; Nishimura, Haruna; Ling, Feng; Su'etsugu, Masayuki; Yoshida, Minoru; Numata, Keiji (Advanced functional materials, 2024)
Mitochondria are vital organelles regulating essential cellular functions. Human mitochondrial DNA (mtDNA) consists of 37 genes, 13 of which encode mitochondrial proteins, and the remaining 24 genes encode two ribosomal RNAs and 22 transfer RNAs needed for the translation of the mtDNA‐encoded 13 proteins. However, mtDNA often impairs the expression and function of these genes due to various mutations, ultimately causing mitochondrial dysfunction. To recover from this desperate condition, developing the technology to supply all mitochondrial proteins encoded by mtDNA at once is an urgent task, but there is no established strategy for this purpose. In this study, a simple yet effective mitochondrial gene delivery system is proposed comprising an artificial peptide inspired by a transmembrane mitochondrial membrane protein. The designed mitochondria‐targeting peptides presented on the carrier surface effectively guide the encapsulated plasmid to the mitochondria, facilitating mitochondrial uptake and gene expression. The developed system successfully delivers exogenous mtDNA to mtDNA‐depleted cells and leads to simultaneous multigene expression, ultimately restoring mitochondrial functions, including the mitochondrial respiration rate. The established multiple gene expression system in each mitochondrion is a game‐changing technology that can accelerate the development of mitochondrial engineering technologies as well as clinical applications for mitochondrial diseases. Polyplexes prepared from artificial peptides inspired by a mitochondrial transmembrane protein efficiently guide the loaded genes, including mitochondrial DNA, to the mitochondria and induce smooth mitochondrial uptake. The delivered mitochondrial DNA expresses all the encoding proteins simultaneously, restoring the mitochondrial functions in the mitochondrial DNA‐depleted cells.